The Warehouse Wellington Zoofari: school visits to Wellington Zoo for conservation‐based learning programmes – an example of effective collaboration between zoos and business. Issue 1 (3rd March 2016) - Hughes, A.; Allan, L.
Abstract : Over the last 2 years, more than 3500 students have participated in The Warehouse Wellington Zoofari (Zoofari), a partnership between Wellington Zoo and The Warehouse, a retailer and iconic New Zealand brand. Zoofari enables children from schools from low socio‐economic areas, who may not otherwise be able to visit, to attend Wellington Zoo for conservation‐based learning sessions. During their visit, the children engage with and learn about the world around them, in order to inspire a long‐term love for nature. This programme has increased the number of Māori and Pasifika children experiencing learning sessions at the Zoo, making it possible to engage further with these underserved ethnic groups. The programme provides the opportunity to connect to the wider community around these students, both through in‐store fundraising in their local communities and with a high level of engagement from parents on the trips to the Zoo. Zoofari is a successful example of an effective collaboration and partnership between zoos and business. Wellington Zoo and The Warehouse are both passionate about making a difference, and Zoofari helps us to connect our local communities with conservation learning and the environment.